Gender charachteristics of entepreneurial activity in the Republic of Kazakhstan - Rakhimzhanova, A. (M. Marikbayev KAZGUU University International School of Economics, 2023)
This study presents the findings of an investigation into the development of women's entrepreneurship and gender equality in Kazakhstan. Utilizing official statistical data, the concentration of women's businesses in the service sector and regional disparities in credit funding were identified. The economic opportunities of businesswomen were evaluated using the "5M" theory, highlighting key policy directions and analyzing access to credit resources and entrepreneurial development programs. While Kazakhstan demonstrates interest in supporting women's entrepreneurship, the study reveals that most state-supported programs lack effectiveness assessment. In-depth interviews with women entrepreneurs from diverse industries shed light on gender-specific challenges and opportunities. The SWOT analysis yielded recommendations for successful development, including support for women on maternity leave, digitalization, improved infrastructure for rural businesswomen, monitoring of women's economic contributions, and male engagement in gender equality efforts. Limitations of the study included insufficient quantitative data and data fragmentation. Nonetheless, the study contributes to the development of integrated approaches to gender analysis in entrepreneurship and provides a necessary scientific and methodological foundation. The innovative application of this integrated approach adds to the existing knowledge and sets the stage for future research on gender characteristics in business.
Keywords: women’s entrepreneurship; gender equality; entrepreneurial activity; 5M theory; qualitative interviews; Kazakhstan